Long term adult visual plasticity after the developmental critical period in genetically determined peripheral visual loss - Otília C. d’Almeida; Joana M. Sampaio; Sónia Ferreira; Eduardo D. Silva; Miguel Castelo-Branco (Heliyon)
Adult neural plasticity within the visual system remains controversial. Starkly opposing views still remain on the ability of the visual system to reorganize in adulthood. Most attempts have focused on testing reorganization upon central visual loss. However, central loss triggers immediate adaptive strategies such as the emergence of new retinal preferential fixation loci, which may preclude plasticity. Moreover, plasticity may be further reduced in later ageing periods. Here we addressed this issue by studying visual plasticity in a genetically determined retinal disorder, Retinitis Pigmentosa, in which peripheral visual loss emerges not long after the critical period, in teenage years. We performed a case-control study with one-to-one matching and used an artificial scotoma approach which carefully simulated the defective visual field of each RP patient on a normal-sighted control. We used as outcomes population receptive field measures to probe long-term plasticity using fMRI retinotopy. We found evidence for reorganization based on pRF size metrics and explained variance of reorganized visual field maps. In sum, visual cortical plasticity triggered by peripheral visual loss occurs beyond the critical period of visual maturation.